1970
DOI: 10.3329/bjo.v14i2.3283
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fine needle aspiration cytology in the diagnosis of Cervical lymphadenopathy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Arul, et al [12] reported 81.75 prevalence of benign lesion. Their observation was similar to those reported by other workers in India and Nepal [20][21][22]. Studies from the western world however reported higher prevalence of malignant neck masses.…”
Section: Discussionsupporting
confidence: 90%
“…Arul, et al [12] reported 81.75 prevalence of benign lesion. Their observation was similar to those reported by other workers in India and Nepal [20][21][22]. Studies from the western world however reported higher prevalence of malignant neck masses.…”
Section: Discussionsupporting
confidence: 90%
“…Lymphadenopathy (abnormality in size, consistency or number of lymph nodes) occurs in response to foreign antigens or by invasion or propagation of either inflammatory or neoplastic cells into the node, depending upon the geographical conditions and socioeconomical set up (Darnal et al, 2005;Bhuyan et al, 2008;Ahmad et al, 2009). In developing countries, infective lymphadenopathy is quite common, mostly due to high prevalence of tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphadenopathy is a clinical manifestation of local and systemic diseases which serves as an excellent clue to the underlying diseases process. [5] In majority of patients, FNAC of lymph nodes serves as an excellent and rapid first line investigation modality to establish the nature of lesion. We conducted a retrospective study in pathology department of SRMS-IMS over a period of one year from January 2013 to December 2013 and 297 patients were selected who presented with palpable, localized or generalized lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%